Navigating Intercultural Awareness with English-Language Movie Genres: English Learners’ Voices - Anis Zayyana; Pratiwi Retnaningdyah; Widyastuti Widyastuti (Prodi Pendidikan Bahasa Inggris, Fakultas Keguruan dan Ilmu Pendidikan, Universitas Islam Darul Ulum Lamongan*, 2024)
In the context of globalization and the increasing accessibility of English-language media, movies have become a significant source for learning about different cultures. As English has become a global lingua franca, exposure to English-language movies offers learners valuable opportunities to engage with diverse cultural narratives, values, and social norms. This study explored the effect of English movies on intercultural awareness among English learners. Particularly, it explored how learners’ preferences for specific movie genres shaped their understanding of cultural differences and similarities. The present study used thematic analysis to analyze interview data from 14 English learners, aged 18 to 25, selected through convenience sampling. Participants were asked about their favorite genres and how they believed these movies influenced their perceptions of other cultures. The findings suggested that English movies significantly contributed to intercultural awareness by offering learners a deeper understanding of cultural practices, communication styles, and societal values. Genres such as comedy and romance helped participants reflect on humor, relationships, and individual freedom, highlighting cultural contrasts between their home cultures and Western norms. Furthermore, animation films introduced learners to unfamiliar cultural traditions and values in an engaging and accessible way. The research also emphasized that movies shaped learners’ intercultural perspectives, both intentionally and unintentionally. This study contributed to the growing field of intercultural communication and highlighted the potential of movies as means of fostering intercultural awareness, offering valuable insights for educators and learners seeking to enhance understanding in cultural diversity.